EVALUATION OF MANDIRI CINTA FARMERS (SARI TANI) VILLAGE PROGRAM IN NAEKAKE "A" VILLAGE, MUTIS SUB-DISTRICT NORTH CENTRAL TIMOR DISTRICT - Yohanes Fritantus; Agustinus Longa Tiza; Yuliana Asten (MAP Observer: Jurnal Penelitian Administrasi Publik, 2023)
This research is motivated by several problem groups where there is a lack of public understanding of the Sari Tani program, lack of socialization related to the Sari Tani program, assistance that is not optimal, and Sari Tani assistance has not been utilized properly so that the Sari Tani program has not been fully implemented. The purpose of this study was to analyze and describe the evaluation of the Independent Village Love Farmer Program (Sari Tani) in Naekake "A" Village, Mutis District, North Central Timor District. The type of research used in this research is descriptive qualitative research with the research focus on Input Indicators, Process Indicators, Output Indicators, Outcome Indicators. Data sources are informants and documents. Data collection techniques are through observation, interviews, and documentation. Data analysis techniques include data collection, data reduction, data presentation, and data verification/conclusion. The results of this study are the first on input indicators, namely by providing financial assistance in the form of loans worth Rp. 5,000,000.00 as a source of supporting funds and basic materials for program implementation; secondly on process indicators is the implementation of socialization to increase the understanding of beneficiary groups; thirdly, on output indicators, namely that the provision of assistance in the form of loan funds was realized and it was also found that there had never been a joint evaluation with the community; and fourth, namely the impact indicator is the increase in people's welfare in the economic field. Keywords: Evaluation, Program, Sari Tani.